Analysis Of Scientific Article Writing Ability - Muhammad Mulia Al-Amien; Dian Hidayati; Didit Haryadi (Universitas Ahmad Dahlan, 2022)
As an educator, it is necessary to have the ability to write scientific articles; as a writer, educators should understand various techniques before writing a scientific article. The author aims to analyze 1) The ability to understand article writing 2) The ability to find research problems 3) The ability to know the types of research 4) The ability to understand research methods 5) The ability to master writing techniques 6) the ability to use excellent and correct language. This research approach is descriptive qualitative. Sources of data are teachers and lecturers. The data collection technique in this research is a test. The data analysis technique uses the Miles and Huberman model. The results showed that the ability to write articles for teachers and lecturers was quite good; this was indicated by the respondents' answers stating 1) aspects of the ability to understand article writing with an average of 59.10% 2) aspects of finding problems in articles with an average of 60.6% 3) aspects of the ability to know the types of research with an average of 58.6% 4) aspects of understanding research methods with an average of 60.10% 5) aspects of mastery of writing techniques 53.0% and 6) aspects of using good and correct language with an average of 56.10%